2020
DOI: 10.1002/jcp.29974
|View full text |Cite
|
Sign up to set email alerts
|

HomeoboxC6 affects the apoptosis of human vascular endothelial cells and is involved in atherosclerosis

Abstract: Apoptosis of vascular endothelial cells (VECs) is highly important in the occurrence and development of atherosclerosis (AS). HomeboxC6 (HOXC6) is expressed in higher levels in multiple malignant tissues, and it influences the malignant biological behavior of the cancer cells. However, the effects of HOXC6 on AS and the apoptosis of VECs have not been fully elucidated. In this study, we demonstrated that HOXC6 expression was increased in aortic wall of AS rats and peripheral blood monocytes of patients with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…For example, BCL2, encodes an outer mitochondrial membrane protein that is anti-apoptotic. The molecule is downregulated in aortic atherosclerotic lesions in rats 49 . VEGFA is a growth factor that induces proliferation and migration of vascular endothelial cells, and is essential for both physiological and pathological angiogenesis, resulting in plaque neovascularization, increased microvessel permeability, and intraplaque hemorrhage 50 , 51 .…”
Section: Discussionmentioning
confidence: 96%
“…For example, BCL2, encodes an outer mitochondrial membrane protein that is anti-apoptotic. The molecule is downregulated in aortic atherosclerotic lesions in rats 49 . VEGFA is a growth factor that induces proliferation and migration of vascular endothelial cells, and is essential for both physiological and pathological angiogenesis, resulting in plaque neovascularization, increased microvessel permeability, and intraplaque hemorrhage 50 , 51 .…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, ECs have crucial roles in atherosclerosis initiation and progression. A previous study by our group suggested that HOXC6 knockdown leads to blunted apoptosis of VECs ( 59 ), and further mechanistic study showed that HOXC6 exerts its function through the phospholipase Cβ/protein kinase Cζ/NF-кB/IL-18 signaling pathway ( 59 ). HOXA1 expression is upregulated in patients with atherosclerosis.…”
Section: A Central Role For Hox Genes In Atherosclerosismentioning
confidence: 97%
“…VECs are one of the primary cellular constituents of the blood vessel wall, and the destruction of their integrity is a pivotal factor in AS pathogenesis [ 5 ]. The dynamic equilibrium between VEC proliferation and apoptosis is the key cytological basis for maintaining VEC integrity and ensuring normal vascular function [ 6 ]. Thus, interrogating novel molecules affecting the proliferation and apoptosis of VEC is important in AS.…”
Section: Introductionmentioning
confidence: 99%